2002
DOI: 10.1055/s-2002-37398
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of Cytosine Methylation Pattern in Response to Water Deficit in Pea Root Tips

Abstract: The correlation between environmental stress and DNA methylation has been studied by following the methylation status of cytosine residues in the DNA of pea root tips exposed to water deficit. DNA methylation was evaluated by two complementary approaches: (i) immunolabelling by means of a monoclonal antibody against 5‐methylcytosine; (ii) MSAP (Methylation‐Sensitive Amplified Polymorphism) to verify if methylation and de‐methylation in response to water deficit may be related to specific DNA sequences. Immunol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
114
0
3

Year Published

2007
2007
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 178 publications
(121 citation statements)
references
References 43 publications
4
114
0
3
Order By: Relevance
“…Effects of environmental variations such as temperature, diseases, light, salinity, ABA and water stress on epigenetic parameters have already been shown in plants (Boyko and Kovalchuk, 2007;Chen and Tian, 2007). The few studies on water stress have analysed overall levels of DNA hypermethylation during osmotic stress in tobacco and potato cell cultures (Kovarik et al, 1997;Sabbah et al, 1995) or during dehydratation in pea root tip cells (Labra et al, 2002). The two fold variation in DNA methylation levels in our system are in agreement with the previous reports.…”
Section: Genotype Specific Changes In Dna Methylation Levels In Resposupporting
confidence: 91%
See 1 more Smart Citation
“…Effects of environmental variations such as temperature, diseases, light, salinity, ABA and water stress on epigenetic parameters have already been shown in plants (Boyko and Kovalchuk, 2007;Chen and Tian, 2007). The few studies on water stress have analysed overall levels of DNA hypermethylation during osmotic stress in tobacco and potato cell cultures (Kovarik et al, 1997;Sabbah et al, 1995) or during dehydratation in pea root tip cells (Labra et al, 2002). The two fold variation in DNA methylation levels in our system are in agreement with the previous reports.…”
Section: Genotype Specific Changes In Dna Methylation Levels In Resposupporting
confidence: 91%
“…While a few studies have demonstrated natural variation of DNA methylation in annual plants (Riddle and Richards, 2002;Vaughn et al, 2007;Zhang et al, 2008) or in organ and cell cultures under osmotic or dehydration stresses (Kovarik et al, 1997;Labra et al, 2002;Sabbah et al, 1995), no data are available in perennial species such as poplar concerning genotypic variation of various epigenetic modifiers, or of their possible correlation with growth and the impact of water deficit. Therefore, the aim of this study is to test a possible role of epigenetic mechanisms in the plasticity of hybrid poplars in response to water deficit.…”
Section: Introductionmentioning
confidence: 99%
“…Dynamic changes in the methylation pattern of genomic DNA upon biotic or abiotic stresses have been reported for several plant species (Chinnusamy and Zhu, 2009). For example, global hypermethylation is induced by 13 drought in pea (Labra et al, 2002). However, stress-induced hypomethylation is observed more frequently.…”
Section: Discussionmentioning
confidence: 99%
“…The important outcome of the cultivation of plant cells under suboptimal conditions is the formation of epialleles, epigenetically modified alleles of a gene (for review, see Finnegan, 2002;ArnholdtSchmitt, 2004). For example, epigenetic changes (mainly in DNA methylation levels) were reported in response to water deficiency (Labra et al, 2002), osmotic stress (Kovarik et al, 1997), and heavy metal presence (Aina et al, 2004).…”
mentioning
confidence: 99%